Congenital Diaphragmatic Hernia: The Side of Diaphragmatic Defect and Associated Nondiaphragmatic Malformations - Grizelj, Ruža; Bojanić, Katarina; Vuković, Jurica; Weingarten, Toby N.; Schroeder, Darrell R.; Sprung, Juraj (American Journal of Perinatology, 2017)
Background Congenital diaphragmatic hernia (CDH) has different clinical presentations depending on whether it is right sided (R-CDH) or left sided (L-CDH). Some have suggested that L-CDH and R-CDH may represent different syndromic phenotypes. This theory would be indirectly supported if different nondiaphragmatic anomalies were associated with laterality. We assessed whether CDH laterality is associated with specific types of nondiaphragmatic anomalies.Methods Cases of CDH were retrospectively identified from five centers, and associated congenital anomalies, prenatal diagnosis, demographics, birth characteristics, and side of the CDH were analyzed. CDH characteristics were summarized according to the absence (isolated) or presence (complex) of nondiaphragmatic malformations.Results Among 228 neonates with CDH, 140 (61%) had isolated CDH and 88 (39%) had complex CDH. Complex CDH was significantly associated with being small for gestational age (odds ratio [95% confidence interval, CI]: 8.3 [1.9–35.7]; p = 0.005) and having L-CDH (odds ratio [95% CI]: 3.6 [1.5–8.9]; p = 0.005). The overall proportion with anomalies differed by side (42% for L-CDH, 23% for R-CDH; p = 0.02), but the rates of anomalies in specific organ systems did not differ.Conclusion The rate of associated nondiaphragmatic anomalies by specific organ system did not differ between L-CDH and R-CDH, which suggests that they represent the same phenotypic entity.
Keywords: congenital diaphragmatic hernia; congenital malformations; left-sided diaphragmatic defect; right-sided diaphragmatic defect